Implementasi Aplikasi COMPACT (Communication on Palliative Care Treatment) Sebagai Upaya Manajemen Diri Pasien Kanker di Sumatera Barat - Rezkiki, Fitrianola; Kartika, Imelda Rahmayunia; Febrina, Cory (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
The prevalence of cancer in West Sumatra Province is around 2.4 per 1000 population, higher than the national prevalence of around 1.7 per 1000 population and really requires the development of appropriate prevention and control programs for cancer, especially in West Sumatra. One of the solutions provided by the Cancer Foundation in Padang City to help overcome the pain of children suffering from cancer is the COMPACT (Communication on Palliative Care Treatment) application. This activity is carried out between June and June. September 2024 in around 20 children with cancer. The activity began with creating the COMPACT application, providing socialization on the application regarding self-management of cancer patients in the form of communication in the form of audio-visual hypnocommunication therapy, guided imagery and murrotal Al-Quran to evaluating the self-management of cancer patients. The evaluation results show that there is a decrease in pain intensity before and after being given pain management intervention through the COMPACT application, namely that there is a decrease in the average pain before and after with an average difference of 2.50-2.00 and there is an increase in self-management so it can be concluded that the use of the application COMPACT can be an option for self-management for cancer patients both at home and in hospitalization. It is hoped that this application will be useful for increasing public knowledge in self-management due to cancer at home.